Effects of a Four-Week High-Dosage Zinc Oxide Supplemented Diet on Commensal Escherichia coli of Weaned Pigs - Johanns, Vanessa C.; Ghazisaeedi, Fereshteh; Epping, Lennard; Semmler, Torsten; Lübke-Becker, Antina; Pfeifer, Yvonne; Bethe, Astrid; Eichhorn, Inga; Merle, Roswitha; Walther, Birgit; Wieler, Lothar H. (Frontiers in Microbiology, 2019)
Strategies to reduce economic losses associated with post-weaning diarrhea in pig farming include high-level dietary zinc oxide supplementation. However, excessive usage of zinc oxide in the pig production sector was found to be associated with accumulation of multidrug resistant bacteria in these animals, presenting an environmental burden through contaminated manure. Here we report on zinc tolerance among a random selection of intestinal E. coli comprising of different antibiotic resistance phenotypes and sampling sites isolated during a controlled feeding trial from 16 weaned piglets: In total, 179 isolates from “pigs fed with high zinc concentrations” (high zinc group, [HZG]: n=99) and a corresponding “control group” ([CG]: n=80) were investigated with regard to zinc tolerance, antimicrobial- and biocide susceptibilities by determining minimum inhibitory concentrations (MICs). In addition, in silico whole genome screening (WGSc) for antibiotic resistance genes (ARGs) as well as biocide- and heavy metal tolerance genes was performed using an in-house BLAST-based pipeline. Overall, porcine E. coli isolates showed three different ZnCl2 MICs : 128 µg/ml (HZG, 2%; CG, 6%), 256 µg/ml (HZG, 64%; CG, 91%) and 512 µg/ml ZnCl2 (HZG, 34%, CG, 3%), a unimodal distribution most likely reflecting natural differences in zinc tolerance associated with different genetic lineages. However, a selective impact of the zinc-rich supplemented diet seems to be reasonable, since the linear mixed regression model revealed a statistically significant association between “higher” ZnCl2 MICs and isolates representing the HZG as well as “lower ZnCl2 MICs” with isolates of the CG (p = 0.005). None of the zinc chloride MICs was associated with a particular antibiotic-, heavy metal- or biocide- tolerance/resistance phenotype. Isolates expressing the 512 µg/ml MIC were either positive for ARGs conferring resistance to aminoglycosides, tetracycline and sulfamethoxazole-trimethoprim, or harbored no ARGs at all. Moreover, WGSc revealed a ubiquitous presence of zinc homeostasis and – detoxification genes, including zitB, zntA and pit. In conclusion, we provide evidence that zinc-rich supplementation of pig feed selects for more zinc tolerant E. coli, including isolates harboring ARGs and biocide- and heavy metal tolerance genes - a putative selective advantage considering substances and antibiotics currently used in industrial pork-production systems.